Laboratory Experiments on Rotation and Alignment of the Analogs of Interstellar Dust Grains by Radiation - Abbas, M. M; Craven, P. D; Spann, J. F; Tankosic, D; LeClair, A; Gallagher, D. L; West, E. A; Weingartner, J. C; Witherow, W. K; Tielens, A. G. G. M (The Astrophysical journal, 2004)
The processes and mechanisms involved in the rotation and alignment of interstellar dust grains have been of great interest in astrophysics ever since the surprising discovery of the polarization of starlight more than half a century ago. Numerous theories, detailed mathematical models, and numerical studies of grain rotation and alignment with respect to the Galactic magnetic field have been presented in the literature. In particular, the subject of grain rotation and alignment by radiative torques has been shown to be of particular interest in recent years. However, despite many investigations, a satisfactory theoretical understanding of the processes involved in grain rotation and alignment has not been achieved. As there appear to be no experimental data available on this subject, we have carried out some unique experiments to illuminate the processes involved in the rotation of dust grains in the interstellar medium. In this paper we present the results of some preliminary laboratory experiments on the rotation of individual micron/submicronsized, nonspherical dust grains levitated in an electrodynamic balance evacuated to pressures of similar to 10 super(-3) to 10 super(-5) torr. The particles are illuminated by laser light at 5320 AA, and the grain rotation rates are obtained by analyzing the low-frequency ( similar to 0-100 kHz) signal of the scattered light detected by a photodiode detector. The rotation rates are compared with simple theoretical models to retrieve some basic rotational parameters. The results are examined in light of the current theories of alignment.